2021
DOI: 10.1002/fsn3.2170
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of soft Sardaigne‐type cheese by using almond gum as a functional additive

Abstract: The effect of almond gum (AG), as natural polysaccharide with high nutritional value and important functional properties, on physicochemical and textural characteristics of Sardaigne‐type cheese was investigated. Response surface methodology (RSM) using Box–Behnken design was applied to determine optimal levels of three selected processing variables such as coagulation temperature (25–45°C), stirring period (20–30 min), and AG concentration (0.25%–0.75%). A 3‐level factorial design was employed to evaluate phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…The Chemical composition of cows and buffalos' soft cheese are shown in table 1 and 2. These results agreed with Ghamgui et al [15] Recorded that the addition of Almond Gum as a functional additive in the Sardaigne-type cheese has improved level of moisture, Lafta et al [16] reported that addition of Gum Arabic increase the moisture content of lowfat soft cheese. The total solids contents in both type of soft cheese samples decrease significantly (P<0.05) with increased concentration of GA combined with ozonated water (0.5).…”
Section: Resultssupporting
confidence: 89%
“…The Chemical composition of cows and buffalos' soft cheese are shown in table 1 and 2. These results agreed with Ghamgui et al [15] Recorded that the addition of Almond Gum as a functional additive in the Sardaigne-type cheese has improved level of moisture, Lafta et al [16] reported that addition of Gum Arabic increase the moisture content of lowfat soft cheese. The total solids contents in both type of soft cheese samples decrease significantly (P<0.05) with increased concentration of GA combined with ozonated water (0.5).…”
Section: Resultssupporting
confidence: 89%
“…This white cheese is a product obtained after milk coagulation (with rennet) and draining (for whey removal). The curd is kept in brine for flavor improvement and preservation [90]. This cheese is reported to have probiotic effect (conferring health benefits) owing to the presence of E. faecalis OB14 and OB15 [91].…”
Section: Soft Cheesementioning
confidence: 99%
“…Una buena puntuación de aceptabilidad indica que los consumidores potenciales estarían dispuestos a comprar este tipo de quesos (Ghamgui et al, 2021). La aceptación es el resultado de la percepción del producto, principalmente en atributos como sabor, olor, apariencia, color y consistencia (Kaczyński et al, 2023).…”
Section: Grado De Satisfacción Con El Queso 1 †1unclassified